The Relationship Between Nutritional Knowledge, Macronutrient Intake, and Body Fat Percentage with Fitness Levels in Karate Athletes - Sagita, Bella; Nurkhoiriyah, Nurkhoiriyah; Harun, Harun (Urecol Journal. Part C: Health Sciences, 2025)
Physical fitness is a vital component that influences the performance of karate athletes. Factors such as nutrition knowledge, macronutrient intake, and body fat percentage are suspected to play an important role in fitness levels. To analyze the relationship between nutrition knowledge, macronutrient intake, and body fat percentage with the fitness level of karate athletes. This study used a cross-sectional design with a sample of 20 karate athletes aged 13–21 years from Inkai Dojo 212, Cirebon Regency. Nutrition knowledge was assessed using a questionnaire, dietary intake was evaluated through a 2×24-hour food recall, body fat percentage was measured using an Omron BIA device, and fitness was assessed using the Yo-Yo Intermittent Recovery Level 1 test. Data analysis was performed using the Spearman test. Most respondents were aged 13–17 years and had a junior high school education level. There was a significant relationship between nutrition knowledge (p<0.000), energy intake (p<0.006), protein (p<0.007), carbohydrate (p<0.041), and body fat percentage (p<0.032) with fitness level. However, no significant relationship was found between fat intake and fitness level (p>0.600). There is a significant relationship between nutrition knowledge, macronutrient intake (except fat), and body fat percentage with the fitness level of karateathletes.